A Conceptual Design for COMBI Dengue Prevention based on an Integrated Psychology and Persuasive Technology Models (International Journal of Innovative Computing, 2022)
Dengue prevention is the best way to prevent dengue outbreaks, as the tagline goes, “prevention is better than cure”. But the challenges lie in sustaining the preventive activity among the community, which commonly only takes place periodically, i.e. when they are dengue outbreaks, with the presence of health officers under the Communication for Behavioural Impact (COMBI) campaign. In this paper, a behaviour change model based on the Transtheoretical Model (TTM) and trigger elements derived from the Fogg Behaviour Model (FBM) is proposed to sustain a community in carrying out preventive activities to prevent dengue. Intervention strategies are added to connect the chosen TTM and FBM. A conceptual design is outlined to further exemplify the proposed model with the identified, which incorporate findings from the persona gathered from a selected community and a mock-up flow. An evaluation plan is described which will be carried out as part of the future work. The proposed model in this paper is hoped to pave the way for sustainable persuasive design.
Keywords: Behavioural change, community, dengue prevention, persuasive design, sustainable